PERANCANGAN SISTEM INFORMASI PENGGAJIAN DOSEN BERBASIS WEBSITE DI AMIK AL MA’SOEM JATINANGOR - Sylvia Novitasari; Firman Hamdani (Jurnal Accounting Information System (AIMS), 2018)
In payroll data processing, AMIK Al Ma'soem still use semi computerization that is using Microsoft Excel application. Based on the observation of the author there are several weaknesses of the system used so far, namely: not integrated data, risk of duplication, edited and deleted data, reporting takes a long time and no lecturer paycheck.In the design of this system using a descriptive method approach in collecting data information needed to create a picture of the situation, incident, or the trend that is developing. While for system design isUML (unified Modeling Language). This system is implemented by using PHP web programming language (Hypertext Preprocessor) and MySQL database.The design of this system is expected to facilitate the users in printing pay slips, printing payroll reports, making assignments, printing report assignments, making absences and lecturers can find information on salary and assignment easily.